Proinflammatory Cytokines and Antiskin Autoantibodies in Patients With Inherited Epidermolysis Bullosa. Issue 42 (October 2015) - Annicchiarico, Giuseppina; Morgese, Maria Grazia; Esposito, Susanna; Lopalco, Giuseppe; Lattarulo, Michele; Tampoia, Marilina; Bonamonte, Domenico; Brunetti, Luigia; Vitale, Antonio; Lapadula, Giovanni; Cantarini, Luca; Iannone, Florenzo
Abstract : Abstract: Epidermolysis bullosa (EB) is a rare disorder characterized by inherited skin adhesion defects with abnormal disruption of the epidermal–dermal junction in response to mechanical trauma. Our aim was to investigate a set of cytokine levels in serum samples from patients suffering from epidermolysis bullosa simplex (EBS), dystrophic epidermolysis bullosa (DEB), and healthy controls (HCs), exploring their potential correlations with antiskin autoantibody titers and disease activity. Forty patients afferent to the Dermatological Ward of Bari City Hospital and 9 HCs were enrolled and subdivided according to the dystrophic (DEB) and simplex forms (EBS). We found a significant increase in interleukin (IL)-1β plasmatic levels of DEB ( P = 0.0224) and EBS ( P = 0.0465) patients compared to HCs; IL-6 levels were significantly higher in DEB than in EBS patients ( P = 0.0004) or HCs ( P = 0.0474); IL-2 levels were significantly increased in DEB compared with EBS ( P = 0.0428). Plasmatic tumor necrosis factor-β and interferon-γ were higher in DEB patients than in HCs ( P = 0.0448 and 0.0229). Conversely, tumor necrosis factor-α was significantly decreased in DEB ( P = 0.0034). IL-5 correlated with anti-BP180 ( r = −0.5018, P = 0.0338), anti-BP230 ( r = −0.6097, P = 0.0122), and anticollagen VII ( r = −0.5166, P = 0.0405) autoantibodies; interferon-γ correlated with anti-BP180 ( r = 0.9633, P < 0.0001), anti-BP230 ( r = 0.9071, P < 0.0001), and anticollagen VII ( r = 0.8619, P = 0.0045) autoantibodies. Score of disease severity was significantly correlated with IL-6 ( r = 0.6941, P = 0.029) and IL-12 ( r = 0.5503, P = 0.0272). The present study supports that EB might be considered a systemic inflammatory disease rather than a skin-limited disorder; clinical disease activity scores could be also integrated by laboratory data such as IL-6 and IL-12 dosage; biotherapies targeting specific cytokine networks probably represent a way to go in the future.